Geographical range and host breadth of Sebacina orchid mycorrhizal fungi associating with Caladenia in south‐western Australia. (8th August 2016) - Phillips, Ryan D.; Barrett, Matthew D.; Dalziell, Emma L.; Dixon, Kingsley W.; Swarts, Nigel D.
Abstract : Specialized mycorrhizal interactions have the potential to limit the geographical range of plant species and contribute to reproductive isolation. We investigated these predictions in Caladenia (Orchidaceae) from south‐western Australia, a group known to have specialized mycorrhizal associations with the genus Sebacina s.l . Sequencing of fungal isolates from 47 of the 136 species of Western Australian Caladenia was undertaken to resolve the geographical range and habitat preferences of mycorrhizal fungal operational taxonomic units (OTUs) and their host breadth in Caladenia . Eight different fungal OTUs were used by Caladenia, with the more frequently detected OTUs occurring in a wide range of habitats and geographical regions. Given the comparatively narrow geographical ranges of most Western Australian Caladenia taxa, this suggests that the geographical ranges of fungal OTUs are unlikely to limit the geographical range of Caladenia spp. Extensive sharing of fungal OTUs between closely related orchid species was detected, suggesting that in the main there is little potential for mycorrhizal fungi to contribute to reproductive isolation between Caladenia spp. Our data mostly support previous work suggesting high mycorrhizal specificity in Caladenia, but this may not be the case in all subgenera, highlighting that Caladenia may offer powerful opportunities for investigating the evolution of specialized mycorrhizal associations.